Synthetic biology encompasses metagenomics, ecosystems, and biodiversity sustainability within its scope - Levin, David B.; Budisa, Nediljko (Frontiers in Synthetic Biology, 2023)
We envision the convergence of synthetic biology (SynBio) and metagenomics as a significant development for the engineering of complex biological systems. The entire biosphere with its diverse life forms can also be considered as a reservoir for evolutionary innovations and a source of modules for SynBio. Metagenomics, which is a large part of biodiversity, should be considered as an important source of modules. The abstraction hierarchy of amalgamating SynBio and metagenomics ("synthetic metagenomics") entails the standardized integration of parts, devices, circuits, and modules into functional chassis. These principles transcend the boundaries of single cell design and apply to the engineering of biodiversity sustainability in multicellular entities, their interconnections, and their dynamics in communities and whole ecosystems. Examples include applications in environmental sustainability, such as analysis of antimicrobial resistance in waste management, bioremediation of oil spills, and degradation of plastics. Future research and experimental interventions will ultimately provide a strong link between bioengineering, metagenomics, microbial consortia, ecosystems, and biodiversity sustainability under the umbrella of synthetic biology.